EXPERT SYSTEM FOR DIAGNOSING TOMATO PESTS AND DISEASES USING FORWARD CHAINING METHOD - Aqilla Fadia Haya; Hafizh Al Karim; Muhammad Rizky Perdana; Andika Sundawijaya (Pusat riset dan Inovasi Nasional, 2022)
Tomato (solanum lyco persicum) is a plant from the solanceae family, native to Central and South America, from Mexico and Peru. Tomatoes have a short life cycle and a height ranging from 1 to 3 meters. Currently, farmers often experience disturbances from pests and diseases of tomatoes due to a lack of knowledge. They do not know how to control it and to eliminate pests that reduce productivity. In identifying diseases in tomato plants we use the Forward Chaining method which is a description that starts from knowing the facts and then matching them with IF and IF-THEN rules. Diseases with a high prevalence in tomatoes are: fruit worms, earthworms, green aphids, white flies, fruit flies (bractrotera) and the diseases are: fusarium wilt, leaf spot disease, bacterial spot, fruit rot. This expert system application provides tomato disease information and disease diagnosis, including control solutions that can be used to reduce the risk of tomato crop damage